First Record of Calydiscoides difficilis (Yamaguti, 1953) Young, 1969 (Monogenoidea, Polyonchoinea, Diplectaniade) on Gills of Three Fish species off Marine Waters of Iraq - Ali A. R. Al-Darwesh; Atheer H. Ali; Hussein A. Saud (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ, 2022)
A parasitological examination of two species of lethrinid fishes; Pink ear emperor Lethrinus lentjan, Spangled emperor L. nebulosus and Areolate grouper Epinephelus areolatus caught in Iraqi marine territorial waters from January to December 2020, revealed that the gills of the fishes were infected with deiplectanid monogenoid, which is identified as Calydiscoides difficilis (Yamaguti, 1953) Young, 1969. This study redescribed the parasite and for the first time described the egg and confirmed that the species has a wide range of dimension resulting from intraspecific variations. The measurements of hard and soft parts of the parasite collected from L. lentjan are smaller than those from L. nebulosus. In addition, the measurements from E. areolatus are close to that from L. lentjan or intermediate between L. nebulosus and L. lentjan. The past record of C. difficilis from L. harak is discussed and hence L. nebulosus and L. lentjan are considered as new records to the Arabian Gulf. Dimensions of the eggs of the parasite in the current study is given here for the first time. The occurrence of C. difficilis from Epinephelidae is considered as a new host family record.